2021
DOI: 10.1002/ejsp.2718
|View full text |Cite
|
Sign up to set email alerts
|

When is it wrong to eat animals? The relevance of different animal traits and behaviours

Abstract: Research suggests that animals’ capacity for agency, experience, and benevolence predict beliefs about their moral treatment. Four studies built on this work by examining how fine‐grained information about animals’ traits and behaviours (e.g., can store food for later vs. can use tools) shifted moral beliefs about eating and harming animals. The information that most strongly affected moral beliefs was related to secondary emotions (e.g., can feel love), morality (e.g., will share food with others), empathy (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…These studies have revealed that judgments of moral concern are influenced by various factors, such as the perceived capacity to experience pain and pleasure of the target being judged (Crimston et al, 2016;H. M. Gray et al, 2007;Leach et al, 2020) and the political ideology of the person making the judgment (Waytz et al, 2019). While these studies have provided first insights into which specific traits of judges and targets influence judgments of moral concern, a more basic question remains unanswered: How important are between-judge and between-target differences for understanding the moral circle?…”
Section: A Variance Component Analysis Of the Moral Circlementioning
confidence: 99%
See 1 more Smart Citation
“…These studies have revealed that judgments of moral concern are influenced by various factors, such as the perceived capacity to experience pain and pleasure of the target being judged (Crimston et al, 2016;H. M. Gray et al, 2007;Leach et al, 2020) and the political ideology of the person making the judgment (Waytz et al, 2019). While these studies have provided first insights into which specific traits of judges and targets influence judgments of moral concern, a more basic question remains unanswered: How important are between-judge and between-target differences for understanding the moral circle?…”
Section: A Variance Component Analysis Of the Moral Circlementioning
confidence: 99%
“…While there is considerable variation in the size of people's moral circle there are also consistent patterns in who we ascribe moral worth to: Typically, we ascribe most moral standing to our family and friends, followed by human in-groups and outgroups, high and low sentient animals, then plants and, finally, villains (e.g., murderers), who are granted the lowest moral standing ; see also Neldner et al, 2018). Thus, different targets are afforded different levels of moral standing and researchers have started to examine which target characteristics predict whether people include them in their moral circle, including sentience (K. Gray et al, 2012;Leach et al, 2020), intelligence (Wilks et al, 2021), species category (Caviola et al, 2019), similarity to humans (Miralles et al, 2019), beauty (Klebl et al, 2021), and moral badness (Piazza et al, 2014).…”
Section: Target and Judge Contributions To Judgments Of Moral Concernmentioning
confidence: 99%
“…These animals are assumed to possess less sophisticated minds compared to other animals (Bastian et al, 2012); leading people to be less concerned about their welfare (Bratanova et al, 2011;Leach et al, 2020;Leite et al, 2019). Taken together, this work shows that moral disengagement surrounding meat eating is characterized by reduced concern for the welfare of food animals, and skepticism about their mental sophistication.…”
Section: Meat Eating and Moral Disengagementmentioning
confidence: 81%
“…These perceptions of animals' mental sophistications or the lack thereof have direct implications for people's judgement of animals' moral standing. Indeed, people rely on intelligence and sentience information to make moral judgements and attribute moral value to individuals (e.g., Bastian et al, 2012;Gray et al, 2007;Leach et al, 2021). Dementalizing food animals makes it easier not to care morally for them, which in turn helps to justify harming or eating them (e.g., Bastian et al, 2012;Hodson et al, 2014;Piazza et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We refer to this difference in attributed moral status between different animals as the moral divide. For instance, Leite et al (2019) demonstrated that people show much less moral concern for low-status animals such as food animals (e.g., pigs) and unappealing wild animals (e.g., snakes) than for highstatus animals such as companion animals (e.g., dogs) and appealing wild animals (e.g., dolphins and chimps) (see also Bratanova et al, 2011;Leach et al, 2021;Piazza, 2020). Although the tendency to value some animals over others has been intensively discussed by philosophers and animal rights advocates, the psychological factors that are potentially related to this phenomenon have received only scant research attention in the psychological literature.…”
mentioning
confidence: 99%